10 Propositions for peace: a review of Braithwaite and D'Costa's Cascades of Violence: War, Crime and Peacebuilding Across South Asia. Issue 3 (2nd July 2020) - Kennedy, Jay P.
ABSTRACT: Braithwaite and D'Costa's Cascades of Violence: War, Crime and Peacebuilding in South Asia delves into the impact and violent legacies of war and violence in South Asia, and selected other areas around the globe. The authors argue that given certain conditions acts of violence are able to cascade throughout society as a response or reaction to violence. Yet, just as violence can proliferate across time and space, given the proper conditions and willing actors peace and non-violent responses to violence can also cascade. In this article I review Braithwaite and D'Costa's new book, giving particular attention to the 10 propositions they develop to explain the cascading of violence, and what can be done to prevent such events. These propositions are the key outcomes of the authors' work around war and peacebuilding in South Asian countries. I conclude with brief thoughts on the empirical, theoretical and practical implications of these propositions.